Identifikasi Kompetensi SMK Program Studi Otomotif dalam Rangka Implementasi Kebijakan Kurikulum 2013 - Gunadi Gunadi; Tawardjono Usman; Beni Setya Nugraha (Jurnal Pendidikan Teknologi dan Kejuruan, 2014)
The objective of this study was to determine; 1) the relevance of competencies in curriculum 2013 with the expectation of the school and the world of business and industry 2) the competencies expected by the school and the world of business and industry for the development of curriculum 2013, and 3) the roles of lecturers and education experts in the implementation of curriculum 2013, especially for the Department of Automotive, Vocational High Schools in Yogyakarta. The study was conducted with survey approach in the industry (authorized workshops), schools (Vocational High School), and universities (YSU and STU). The data collection was conducted using documentation, questionnaires, and interviews. The data was analysed using quantitative descriptive statistics. The results showed that: the relevance of competencies in curriculum 2013 with the expected competencies was 82% to 89%. The competencies expected by the schools and the world of business and industry consists of drawing with autocad and / or 3D max, spooring, as well as maintaining hidroulik power steering, measuring and analyzing vehicle emissions, maintaining hydraulic power steering (HPS), analyzing damage in the system of wiring diagram, and conducting damage diagnosis. The lectures’ contribution in the socialization and  implementation aspects were categorized as good with the mean scores of 73 and 39.5 respectively.